2019
DOI: 10.1007/s10549-019-05181-4
|View full text |Cite
|
Sign up to set email alerts
|

Progression-free survival (PFS) and toxicities of palbociclib in a geriatric population

Abstract: Purpose: Over 40% of newly diagnosed metastatic breast cancer patients are ≥ 70 years-old however this population is less likely to be represented in clinical trials. The objective of this study was to analyze PFS, dose reductions, dose delays and toxicity in a geriatric population receiving palbociclib in a non-trial setting.Methods: Patients with metastatic breast cancer receiving palbociclib in any line of therapy were identified from a cohort of 845 patients at a large academic institution. Dose delays, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 23 publications
(40 reference statements)
4
27
0
Order By: Relevance
“…No substantial differences in incidence and severity of AEs were seen between the two groups of women receiving palbociclib combined with letrozole or fulvestrant, and no increased toxicity was observed in patients >65 years compared with a younger population, in line with the recently reported data on a large geriatric population receiving palpociclib in a non-trial setting. 43 Nevertheless, we experienced fewer dose reductions (17% of patients in the whole population, most frequently due to neutropenia), compared with randomised phase III trials (36% and 34% of patients in PALOMA-2 and PALOMA-3, respectively) even if we had more cycle delays, as often happens in clinical practice. As previously reported, this did not seem to affect treatment effectiveness.…”
Section: Discussionmentioning
confidence: 81%
“…No substantial differences in incidence and severity of AEs were seen between the two groups of women receiving palbociclib combined with letrozole or fulvestrant, and no increased toxicity was observed in patients >65 years compared with a younger population, in line with the recently reported data on a large geriatric population receiving palpociclib in a non-trial setting. 43 Nevertheless, we experienced fewer dose reductions (17% of patients in the whole population, most frequently due to neutropenia), compared with randomised phase III trials (36% and 34% of patients in PALOMA-2 and PALOMA-3, respectively) even if we had more cycle delays, as often happens in clinical practice. As previously reported, this did not seem to affect treatment effectiveness.…”
Section: Discussionmentioning
confidence: 81%
“…The teams caring for Grace and Hazel made certain both women understood the risk of neutropenia with palbociclib—including how it differs from chemotherapy-induced neutropenia—and encouraged them to monitor their temperature and report any instances of fever above 100.4°F ( Sammons et al, 2017 ; Thill & Schmidt, 2018 ; US Department of Health and Human Services, 2017 ). In keeping with clinical trial and real-world evidence of an increased risk of neutropenia in older patients ( Clifton et al, 2019 ), Hazel experienced persistent neutropenia and leukopenia, which were addressed through treatment delay and dose modification. Nonhematologic AEs in both patients were effectively addressed through supportive measures, including medication and lifestyle changes.…”
Section: Discussionmentioning
confidence: 96%
“…Subgroup analyses from the PALOMA trials and real-world data have demonstrated that the efficacy and safety of palbociclib-based combination therapy is consistent regardless of age or menopausal status ( Clifton et al, 2019 ; Cristofanilli et al, 2016 ; Pfizer Inc, 2019a ; Loibl et al, 2017 ; Rugo et al, 2018 ). As a result, 74-year-old Hazel and 36-year-old Grace were both prescribed the recommended palbociclib starting dose of 125 mg ( Pfizer Inc, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of Phase II and III randomized clinical trials, older patients treated with palbociclib were more likely to experience neutropenia, leukopenia, anemia, back pain, asthenia, and infections, whereas older patients treated with abemaciclib were more likely to experience neutropenia, leukopenia, anemia, and diarrhea [ 37 ]. Older patients have also been shown to have more dose reductions and delays than younger patients [ 38 ].…”
Section: The Predisposing Precipitating and Perpetuating (3p) Momentioning
confidence: 99%